Studi Kinerja Teoritis Pengkondisian Udara Menggunakan R32, R290 Dan R410a - Sengge, James Roland; Dwinanto, Matheus M.; Tobe, Adi Y. (Universitas Nusa Cendana, 2022)
The use of more environmentally friendly refrigerants in air conditioning systems has become a central demand and issue in the future. This article presents the simulation results of the comparison of the use of R32 (difluoromethane), R290 (propane) and R410A (difluoromethane+pentafluoroethane) on the performance of air conditioning systems. The thermodynamic analysis of the system using the two refrigerants used the CoolTools version 1.0 software at several variations of the evaporation temperature, with the condensation temperature held constant. The important quantities analyzed are heat release in the condenser, compressor power, and coefficient of performance. The results of this study indicate that the performance of air conditioning using R290 is higher than the use of R32 and R410A while the lowest coefficient of performance is owned by air conditioning using R410A. In addition, R290 is more environmentally friendly than R32 and R410A, so the use of R290 is highly recommended